Progressive Symptom-Associated Prefrontal Volume Loss Occurs in First-Episode Schizophrenia but not in Affective Psychosis - Ohtani, Toshiyuki (Brain Struct Funct, 2018)
Although smaller gray matter volumes (GMV) in the prefrontal cortex (PFC) in schizophrenia and bipolar disorder have been reported cross-sectionally, there are, to our knowledge, no reports of longitudinal comparisons using manually drawn, gyrally-based ROI, and their associations with symptoms. The object of this study was to determine whether first-episode schizophrenia (FESZ) and first-episode affective psychosis (FEAFF) patients show initial and progressive PFC GMV reduction in bilateral frontal pole, superior frontal gyrus (SFG), middle frontal gyrus (MFG), and inferior frontal gyrus (IFG) and examine their symptom associations. Twenty-one FESZ, 24 FEAFF and 23 healthy control subjects (HC) underwent 1.5T MRI with follow-up imaging on the same scanner ~ 1.5 years later. Groups were strikingly different in progressive GMV loss. FESZ showed significant progressive GMV loss in the left SFG, bilateral MFG, and bilateral IFG. In addition, left MFG and/or IFG GMV loss was associated with worsening of withdrawal-retardation and total BPRS symptoms scores. In contrast, FEAFF showed no significant difference in GMV compared with HC, either cross-sectionally or longitudinally. Of note, FreeSurfer run on the same images showed no significant changes longitudinally.